PERAN PEKERJA SOSIAL DALAM PELAKSANAAN PENGANGKATANANAK WARGA NEGARA INDONESIA OLEH WARGA NEGARA ASING DI YAYASAN SAYAP IBU CABANG JAKARTAANAK WARGA NEGARA INDONESIA OLEH WARGA NEGARA - Lisnawati, Iis; Sekar, Dwi Amalia Chandra (UI Scholars Hub, 2020)
This paper discusses the role of social worker in implementing the removal of neglected children of Indonesia citizens by foreign citizens (intercountry adoption) in Yayasan Sayap Ibu Branch of Jakarta. This paper also uses qualitative approach and descriptive methods. The data collection carried out by observation and in depth interviews with ten informants consists of social workers, coordinator for child alleviation, four people of prospective parents, and four people of related ministries/institutions. The results of this paper describes: (1) the role of social workers as enabler, broker, mediator, negotiator, advocate, and also other roles, which as administrator and counsellor; (2) barriers from prospective adoptive parents in the form of incomplete documents, refusal from adoptive parents to adopted children, prospective parents are less cooperative. The barriers from inside institutions are social worker welfare and less responsive work environments for social workers. Meanwhile, limited knowledge and skills in digging information, limited foreign language skills, and also change in official/officer in related ministries/institutions are the barriers for social workers in Yayasan Sayap Ibu Branch of Jakarta.